The EU in Georgia: Building Security? - Freire, Maria Raquel (2013)
This article addresses the European Union (EU)’s security actorness, explaining its meaning, identifying the factors that are constitutive to the concept, and analysing whether the EU is becoming a mature security provider in Georgia. The paper argues that despite the successful assessments of the EU Monitoring Mission in the context of CSDP development, the mission’s main contribution to the EU’s consolidation as a mature security actor and of a new regional status quo in the South Caucasus is centred on the complementary and comprehensive nature of the different EU tools deployed on the ground, in line with what we see as the ‘coming of age’ of the EU as a mature security actor.